2023
DOI: 10.1101/2023.05.26.542311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sorgoleone degradation by sorghum-associated bacteria; an opportunity for enforcing plant growth promotion

Abstract: Metabolite exchange between plant roots and their associated rhizosphere microbiomes underpins plant growth promotion by microbes. Sorghum bicolor is a cereal crop that feeds animals and humans and is used for bioethanol production. Its root tips exude large amounts of a lipophilic benzoquinone called sorgoleone. Sorgoleone is an allelochemical that suppresses the growth of competing plant seedlings and is mineralized by microbes in soil. As an avenue to understand how sorghum and its root microbiome may be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Alternatively, this observation could be explained by strain-level competition for resources. Ongoing work from our group suggests that Streptomyces are good solubilizers of a wide variety of novel metabolites (Oda et al, 2023). We propose that Streptomyces may directly use sorghum-specific root exudate compounds such as sorgoleone and introduction of other utilizers creates competition for these carbon sources.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, this observation could be explained by strain-level competition for resources. Ongoing work from our group suggests that Streptomyces are good solubilizers of a wide variety of novel metabolites (Oda et al, 2023). We propose that Streptomyces may directly use sorghum-specific root exudate compounds such as sorgoleone and introduction of other utilizers creates competition for these carbon sources.…”
Section: Discussionmentioning
confidence: 99%
“…Global proteomics results showed that all four gene members of the Srg gene cluster implicated in sorgoleone catabolism were readily identified and were more abundant in culturing conditions with sorgoleone compared to acetate. 18 From this pathway, OH685_09420 was identified as a protein binder of sorgoleone through competitive labeling with SoDA-PAL and purified sorgoleone. Recent technological advances in structural bioinformatics software, which has enabled faster and more accurate protein structure prediction through artificial intelligence, provide new opportunities to combine experimental and computational approaches for elucidation of protein functions and interactions.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is encoded by a gene cluster containing a putative monooxygenase, two putative α/β fold hydrolases, and a cytosine deaminase (Figure 5A). 18 Initially our global proteomic analysis revealed a marked difference in coverage of this pathway between carbon sources, where the lowest pathway member coverage was observed in the acetate culture (A), with higher coverage observed with the acetate to sorgoleone (AS) culture and sorgoleone only culture (S) (Figure 5B). This trend was further reinforced with competitive SoDA-PAL labelling of the acetate to sorgoleone cultures, as competition was observed for all four pathway members with the two putative α/β fold hydrolases (OH685_09415, OH685_09420) exhibiting significant competition, implying a direct interaction of those protein targets with sorgoleone (Figure 5C).…”
Section: Soda-pal Enriches a Subset Of The Proteome And Enables Ident...mentioning
confidence: 94%
See 2 more Smart Citations